Assessing causes of inter- ethnic conflict in Ethiopia: Emphasis on Anuak and Nuer conflicts in Gambella Regional State - Tasgara, Asafa (International Journal of Rehabilitation and Special Education (IJRSE), 2021)
This study was directed on causes of inter- ethnic conflict in Ethiopia by stress on Anuak and Nuer conflicts in Gambella Regional State of Ethiopia. The general objective of this paper was an assessment on the causes of inter-ethnic conflict among Anuak and Nuer ethnic groups in Gembela regional state. The data was collected based on secondary sources. The researcher employed descriptive and explanatory types of research design. The findings from this study confirm that questions regarding property and land right, language and access to weapons are the major causes of conflict between the two ethnic groups. In addition, the paper found the solution for the Anuak and Nuer conflict would be, development initiatives along the Ethiopia and Sudanese border, full pledged arms control along the Ethiopia and Sudanese border could be an important factor in minimizing conflict and causalities in the future. The two groups could reach similar agreements, provided that they are offered the right opportunity to talk to each other, discuss their problems and apply traditional mechanisms of conflict resolution.